Potential for Rehabilitation Management Utilizing A Theory of Planned Behavior Approach Via Telehealth in Home Treatment-Based Diabetes Management: A Literature Review - Fahmi Wildana; Lutfian; Aufa Azizah; Essarani Oktaviana (Jurnal Ilmiah Kesehatan)
iabetes Mellitus is a metabolic disorder characterized by insufficient insulin